Hemotropic Mycoplasma ovis infection in goats with concurrent gastrointestinal parasitism in Malaysia - Jesse, Faez Firdaus Abdullah; Bt Abu Jazid, Nurul Hafizah; Mohamme, Konto d; Tijjani, Abdulnasir; Chung, Eric Lim Teik; Abba, Yusuf; Sadiq, Muhammad Abubakar; Saharee, Abdul Aziz (Journal of Advanced Veterinary and Animal Research, 2015)
Hemotropic Mycoplasmosis is common in sheep and goats worldwide, which leads to huge economic losses. In this study, ten goats each were sampled from five herds belonging to the Ladang Angkat, Faculty of Veterinary Medicine (FVM) for the assessment of Mycoplasma ovis infection and concomitant intestinal parasites burden. Giemsa stain and Modified McMaster techniques were used to study the hemotropic mycoplasmosis and gastrointestinal parasite burden, respectively. Questionnaires were equally administered to each farmer and a fly trap was used to trap biting flies around the goat herds. Out of 50 samples analyzed, 94.0% ( n = 47/50) were positive for M. ovis infection. Among the positive samples, 93.6% (n=44/47) were mild infection while 6.4% (n=3/47) were moderate infection, with highest infection rate of 38.5% parasitemia. There was a significant association (P<0.05) between infection status and parasites burden. However, there was a weak positive correlation (r=0.107, P=0.460) between M. ovis infection rates and parasitic burden. Though a high occurrence rate of M. ovis was observed among the infected goats, the levels of parasitemia were generally mild. http://dx.doi.org/10.5455/javar.2015.b119